2021
DOI: 10.1111/tpj.15304
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic geraniol and citronellol biosynthesis require a Nudix hydrolase in rose‐scented geranium (Pelargonium graveolens)

Abstract: Summary Geraniol, citronellol and their esters are high‐value acyclic monoterpenes used in food technology, perfumery and cosmetics. A major source of these compounds is the essential oil of rose‐scented geraniums of the genus Pelargonium. We provide evidence that their biosynthesis mainly takes place in the cytosol of glandular trichomes via geranyl monophosphate (GP) through the action of a Nudix hydrolase. Protein preparations could convert geranyl diphosphate (GDP) to geraniol in in vitro assays, a process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 74 publications
(185 reference statements)
0
11
0
Order By: Relevance
“…In addition, the content of borneol generated from BP as substrate was considerably higher than that from BPP, indicating potential differences in the phosphatases that hydrolyze BPP and BP. Recent findings have shown that Nudix hydrolase can catalyze the production of GP and FP from GPP and FPP, respectively, in certain plants such as roses and Pelargonium graveolens , which were then hydrolyzed by hydrolases of broad substrate specificity to produce geraniol and farnesol (Bergman et al., 2021; Sun et al., 2020). Therefore, we hypothesize that Nudix hydrolase may also be involved in the biosynthesis of borneol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the content of borneol generated from BP as substrate was considerably higher than that from BPP, indicating potential differences in the phosphatases that hydrolyze BPP and BP. Recent findings have shown that Nudix hydrolase can catalyze the production of GP and FP from GPP and FPP, respectively, in certain plants such as roses and Pelargonium graveolens , which were then hydrolyzed by hydrolases of broad substrate specificity to produce geraniol and farnesol (Bergman et al., 2021; Sun et al., 2020). Therefore, we hypothesize that Nudix hydrolase may also be involved in the biosynthesis of borneol.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes primarily hydrolyze primary metabolites including nucleoside diphosphates, nucleoside triphosphates, coenzyme A, NAD(P)H, and capped mRNAs (Yoshimura & Shigeoka, 2015). In recent years, Nudix hydrolases have also been implicated in plant terpenoid metabolism, e.g., catalyzing the hydrolysis of GPP, isopentenyl diphosphate (IPP), dimethylallyl diphosphate (DMAPP), and farnesyl diphosphate (FPP) to generate the corresponding monophosphate products (Bergman et al, 2021;Conart et al, 2023;Henry et al, 2018). Notably, the Nudix hydrolase RhNUDX1 (Rosa 9 hybrida) converts GPP to geranyl phosphate (GP), which is subsequently hydrolyzed to geraniol by a phosphatase (Magnard et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest a possible new case for monoterpene biosynthesis, in which a cytosolic TPS might utilize MVA-derived GPP for monoterpene production (MVA-TPS case). This MVA-TPS case might be more ubiquitous than the special MVA-NUDX case for geraniol biosynthesis, as a nudix hydrolase capable of hydrolyzing GPP into geraniol was only characterized for rose hybrids and Pelargonium graveolens (Bergman et al ., 2021) so far, while both TPS and MVA pathway are widely distributed in higher plants.…”
Section: Discussionmentioning
confidence: 99%
“…Citronellol biosynthesis has been demonstrated to derive from geraniol in Caenorhabditis plicata, (Haiyang Xu et al 2017) and a similar pathway in pelargonium can be suggested in accordance with the characterization of a geraniol synthase in the species (Blerot et al 2018). Nevertheless, this pathway is still under debate (Bergman M et al 2021). Citronellol is not an end-product but undergoes further modifications through esterification or glycosylation to produce several citronellyl esters and citronellol glycosides.…”
Section: Introductionmentioning
confidence: 99%